Tata Kelola Dana Desa dalam Rangka Implementasi Undang–Undang Nomor 6 Tahun 2014 Tentang Desa di Kecamatan Krian Kabupaten Sidoarjo - Fauzi, Achmad (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
The village is a collection of people who live together or a region, which has a government organization with a set of rules that you define yourself, and under the leadership of the village were selected and assigned its own. Since the enactment of Law No. 6 of 2014 on Village hereinafter called the Village Law. In the course of this village there is a translation of the Act detailing government regulations on the management of village finances. Of PP 43 in 2014 and converted into PP 47 2015 and of PP PP 60 in 2014 to 8 in 2016, there are some things that lead to the necessity of adjusting the legal basis on the village's financial management practices. The problems of this research focuses on the mechanism of channeling funds Krian village in the district of Sidoarjo regency and use of village funds to realize good governance in Sidoarjo. And finally, this study aims to Analyze fund disbursement mechanism villages to villages in Sidoarjo and analyze procedures and the implementation of the use of funds village in Sidoarjo. The method used in this study is a socio legal research approach jurisprudence which use the social sciences, by applying social science perspective to the study of law. Including legal sociology, legal anthropology, legal history, psychology and law, political science studies judiciary, comparative linguistics, as well as other scientific. Legal research is performed to find a solution to the legal issues that arise. The results to be achieved is to provide a prescription of what should be.